Examining the Influence of Coordination on Employee Performance - Dadang Syaputra; Faudunasokhi Telaumbanua; Raju Gobal; Salam Irianto Nadeak; Syafriyandi Syafriyandi (Advances in Human Resource Management Research, 2026)
Purpose: Drawing on Organizational Coordination Theory and Human Resource Management perspectives, this study examines the effect of coordination on employee performance at the Percut Sei Tuan Sub-District Office, Deli Serdang Regency. Research Method: A quantitative explanatory design was employed, using a saturated sampling technique that included all 48 employees of the sub-district office. Data were collected through structured questionnaires and analyzed using validity and reliability tests, simple linear regression, correlation analysis, the coefficient of determination, and t-tests in SPSS. Results and Discussion: The findings indicate that coordination has a positive and significant effect on employee performance. The regression results indicate that improved coordination is associated with higher employee performance (β = 0.453, p = 0.003). The correlation coefficient (r = 0.424) suggests a moderate relationship between the variables, while the coefficient of determination (R² = 0.180) indicates that coordination explains 18% of the variance in employee performance. Implications: The findings highlight the importance of strengthening communication, task integration, and inter-unit collaboration to improve employee performance and the effectiveness of public service. Originality: This study contributes to the public administration literature by providing empirical evidence on the role of coordination in enhancing employee performance within a local government institution.